Translanguaging as an instructional method in science and mathematics education in English second language classroom contexts - Nhongo, Raphael; Tshotsho, Baba Primrose (Independent Institute of Education, 2022)
The teaching of science and mathematics in African languages has been debated at various academic platforms that include seminars, conferences and publications where the major concern that has recurred is how it could be possibly done. The questions raised are mainly about the inadequacies of these African languages ranging from orthographies, terminologies to reading materials. For the reading materials to be produced there has to be agreed upon terminologies and the thrust of this paper is to delve on how such terminologies can be produced and how the teaching and learning can be done in African languages. Four secondary schools, two rural and two urban, were used as case studies, two in Bulawayo, and the other two in Matabeleland South province in Zimbabwe. The perceptions of science and mathematics teachers about translanguaging as a method of teaching science and mathematics were sought through interviews from eight teachers, that is, two from each of the four schools. The results showed that teachers have always been applying translanguaging as an instructional method in the teaching of science and mathematics although they were not aware that translanguaging is a concept that can be singled out amongst other strategies of instruction. The paper concludes that adopting translanguaging as a teaching method in bilingual classroom contexts aids learners’ cognition thereby enhancing comprehension of concepts better than when only English language is used in teaching and learning.